Arachnoid fibrosis in the cerebellopontine angle of primary trigeminal neuralgia: a histopathological study - Siqiang Tang; Mufang Huang; Jiajie Wu; Yexin Li; Kaiyuan Jiang; Peng Deng (Frontiers in Neurology)
ObjectiveThis study aimed to evaluate differences in the arachnoid membrane of the cerebellopontine angle (CPA) cistern between patients with trigeminal neuralgia (TN) and trauma patients without TN, providing novel insights into the pathogenesis of TN.MethodsArachnoid specimens were collected from patients with primary TN undergoing their first microvascular decompression at the Neurosurgery Department of Shaoyang Central Hospital between January 2021 and September 2024 (study group) and from patients with posterior cranial fossa trauma undergoing surgery during the same period (normal control group). Specimens from both groups were subjected to hematoxylin–eosin (HE) staining and picric acid-Sirius red staining. Morphological thickness and collagen fiber thickness in the arachnoid membrane were measured under polarized light microscopy and then compared and statistically analyzed.ResultsThe study included 41 patients with primary TN and 38 normal control subjects. In the TN group, the mean thickness of the entire arachnoid layer in the CPA cistern was 87.86 ± 9.34 μm, and the mean thickness of collagen fibers was 53.95 ± 8.90 μm. In the control group, these values were 62.55 ± 1.55 μm and 33.50 ± 3.60 μm, respectively. The differences in both arachnoid thickness (p < 0.001) and collagen fiber thickness (p < 0.001) between the groups were statistically significant.ConclusionPatients with TN exhibited significant arachnoid fibrosis and thickening in the CPA cistern, primarily due to an increase in collagen fibers. These findings suggested a potential pathological mechanism underlying TN.